Mitochondrial Probe Methyltriphenylphosphonium (TPMP) Inhibits the Krebs Cycle Enzyme 2-Oxoglutarate Dehydrogenase - Elkalaf, Moustafa; Tůma, Petr; Weiszenstein, Martin; Polák, Jan; Trnka, Jan (PLoS One, 2016)
Methyltriphenylphosphonium (TPMP) salts have been widely used to measure the mitochondrial membrane potential and the triphenylphosphonium (TPP+) moiety has been attached to many bioactive compounds including antioxidants to target them into mitochondria thanks to their high affinity to accumulate in the mitochondrial matrix. The adverse effects of these compounds on cellular metabolism have been insufficiently studied and are still poorly understood. Micromolar concentrations of TPMP cause a progressive inhibition of cellular respiration in adherent cells without a marked effect on mitochondrial coupling. In permeabilized cells the inhibition was limited to NADH-linked respiration. We found a mixed inhibition of the Krebs cycle enzyme 2-oxoglutarate dehydrogenase complex (OGDHC) with an estimated IC50 3.93 [3.70-4.17] mM, which is pharmacologically plausible since it corresponds to micromolar extracellular concentrations. Increasing the lipophilic character of the used TPP+ compound further potentiates the inhibition of OGDHC activity. This effect of TPMP on the Krebs cycle ought to be taken into account when interpreting observations on cells and mitochondria in the presence of TPP+ derivatives. Compounds based on or similar to TPP+ derivatives may also be used to alter OGDHC activity for experimental or therapeutic purposes.
Keywords: Glutamate Dehydrogenase; Citrate (si)-Synthase; ketoglutarátdehydrogenasový komplex; Citric Acid Cycle; glutamátdehydrogenasa; krysa rodu Rattus; Membrane Potential, Mitochondrial; zvířata; Malate Dehydrogenase; potkani Wistar; oniové sloučeniny; buněčné linie; citrátsynthasa; kosterní svaly; malátdehydrogenasa; Cell Line; Onium Compounds; Pyruvate Dehydrogenase Complex; Rats, Wistar; Triphenylmethyl Compounds; Muscle, Skeletal; citrátový cyklus; pyruvátdehydrogenasový komplex; Rats; tritylové sloučeniny; Animals; Ketoglutarate Dehydrogenase Complex; Mitochondria, Muscle; membránový potenciál mitochondrií; svalové mitochondrie; isocitrátdehydrogenasa; Isocitrate Dehydrogenase